Physical Properties of Lignin Added Wood Flour-Polypropylene Composites: A Comparison of Direct and Solvent Mixing Techniques - Behrooz, Rabi; Younesi Kordkheili, Hamed; Kazemi Najafi, Saeed (Asian Journal of Chemistry, 2011)
In this study, lignin addition (by two mixing techniques) and its influence on the long-term water absorption and thickness swelling of wood-plastic composites (WPCs) were investigated. Lignin powder extracted from Kraft black liquor mixed with the wood flour with ratios of 0, 2, 5 and 10 % (based on wood dry weight) by direct and solvent techniques. The composites were manufactured by hot press method after mixing of the wood flour, lignin compound with polypropylene including maleated polypropylene (0 and 2 %) in an internal mixer. The results indicated that water absorption and associated thickness swelling were decreased by increasing of lignin content in all of the studied composites. Also the results showed that the composites were produced by solvent mixing exhibit less water absorption and associated thickness swelling rather those were produced by direct mixing method. Application of maleated polypropylene in the composites decreased water absorption and thickness swelling as well as water absorption coefficients. The result also indicated that the lignin can be used as co-compatibilizer of maleated polypropylene in the wood-plastic composites. Water absorption of the studied composites was proved to follow the kinetics of Fickian diffusion process.